The spirit of the sword and spear - Pearce, Mark (Cambridge University Press (CUP), 2013)
From the Norse sagas or the Arthurian cycles, we are used to the concept that the warrior’s weapon has an identity, a name. In this article I shall ask whether some prehistoric weapons also had an identity. Using case studies of La Tène swords, early Iron Age central and southern Italian spearheads and middle and late Bronze Age type Boiu and type Sauerbrunn swords, I shall argue that prehistoric weapons could indeed have an identity and that this has important implications for their biographies, suggesting that they may have been conserved as heirlooms or exchanged as prestige gifts for much longer than is generally assumed, which in turn impacts our understanding of the deposition of weapons in tombs, where they may have had a ‘guardian spirit’ function.